Engenharia de requisitos e modelagem de software: um estudo de caso em uma academia universitária de musculação - SANTOS, Raonner Bruno Rodrigues dos (2024)
This study explores the initial stages of Software Engineering (SE), focusing on Requirements Engineering (RE) and Software Modeling in the context of a university gym. Using qualitative methods, requirements were elicited through interviews, resulting in a validated Requirements List. Unified Modeling Language (UML) diagrams, including Use Case and Class diagrams, were developed to illustrate system interactions and structures. The study establishes a solid foundation for the gym management system, with future work including prototyping and user testing for refinement.